Development of improved bottleneck-based heuristic for re-entrant flow shop with dominant machine at M1 and M4 - Mohd Fidzwan, Md Amin Hamzas; Ahmad Bareduan, Salleh; Liyana, Tajul; Mohd Sabri, Hussin; Zailani, Zainal Abidin; Hasnul, Hadi (Praise Worthy Prize S.r.l., 2013)
Link to publisher's homepage at http://www.praiseworthyprize.com/